2011
DOI: 10.1177/0269216310386279
|View full text |Cite
|
Sign up to set email alerts
|

Spinal opioids in adult patients with cancer pain: A systematic review: A European Palliative Care Research Collaborative (EPCRC) Opioid Guidelines Project

Abstract: There are few RCTs and these are of very low quality. As a result, they provide weak recommendation for using spinal opioids in adult cancer patients. Further studies are clearly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 57 publications
(146 reference statements)
0
14
0
Order By: Relevance
“…Deciding on the use of these interventions requires an estimation of prognosis and an assessment of risks (contraindications to spinal procedures in patients with risk of bleeding, infection, or local tumor burden) compared with the potential benefits in patients whose pain is inadequately managed. Much of the data on outcomes are based on uncontrolled studies; therefore, more studies are needed to evaluate the efficacy and safety of spinal opioids …”
Section: Pain Management: Nonopioidmentioning
confidence: 99%
See 1 more Smart Citation
“…Deciding on the use of these interventions requires an estimation of prognosis and an assessment of risks (contraindications to spinal procedures in patients with risk of bleeding, infection, or local tumor burden) compared with the potential benefits in patients whose pain is inadequately managed. Much of the data on outcomes are based on uncontrolled studies; therefore, more studies are needed to evaluate the efficacy and safety of spinal opioids …”
Section: Pain Management: Nonopioidmentioning
confidence: 99%
“…Much of the data on outcomes are based on uncontrolled studies; therefore, more studies are needed to evaluate the efficacy and safety of spinal opioids. 90…”
Section: Interventionsmentioning
confidence: 99%
“…14 The review concluded that there are few RCTs and that these are of low quality, generally due to small sample size, variable study design and methodological limitations thus producing weak evidence. They analysed the accumulated incidence data from the uncontrolled trials, and concluded that spinal opioid therapy may be effective for treating cancer pain that has not been adequately controlled by systemic treatment.…”
Section: Cancer Painmentioning
confidence: 99%
“…Using the quality of evidence hierarchy developed by the U.S. Preventive Services Task Force, Patel and coworkers (8) found both level II‐3 and level III evidence supporting the use of IT infusion systems for chronic noncancer pain. Kurita and coworkers (9) performed a systematic review to analyze analgesic efficacy and side‐effects of spinal opioids in adult cancer patients previously treated with systemic opioids. These authors identified nine RCTs, two nonrandomized cohort studies, 28 uncontrolled prospective studies, and five case series evaluating these issues.…”
Section: Concerns Over Efficacymentioning
confidence: 99%